Governança corporativa em fundações mantenedoras de instituições de ensino superior privadas: um estudo do Sul de Minas Gerais - Paiva, Gilmar Martins de (2019)
The main objective of this research was to investigate whether the Foundations of Higher Education Institutions (IES) of Southern Minas Gerais adopt the Good Corporate Governance Practices recommended by the Brazilian Institute of Corporate Governance (IBGC). The specific objectives were directed to research in the bibliography studies and publications regarding IBGC's good corporate governance practices for private Foundations. The object of study is the Private IES Foundations, created by the constitution of a patrimony to serve a certain purpose of public utility or to act for the benefit of society, characterized by their charitable ends, being the central nucleus the patrimony, composing the so-called "third sector", made up of non-profit and non-governmental organizations, with the purpose of operating services of public interest, being maintained with public and private resources. The guiding question of the research was: Do the Private IES Foundations in the South of Minas Gerais use the best Corporate Governance practices suggested by IBGC? As for the methodological procedures, a quantitative approach was adopted with the application of a questionnaire structured according to the governance pillars defined by IBGC, IBGC (2016), "Guide to Best Practices for Organizations in the Third Sector: Associations and Foundations". The results of the survey showed that the IES Private Foundations, responding to the questionnaire of the South of Minas Gerais, generally adopt 72.98% of the good corporate governance practices recommended by the "Best Practices Guide for Third Sector Organizations: Associations and Foundations ". Regarding the pillars of corporate governance of the aforementioned Guide, the Curator Council adopts 71.15%, Organizational Management 71.83%, Independent Audit 78.03%, Fiscal Council 82.50% and Conduct and Conflict of Interest 69.64 % of best practices recommended by IBGC Guide (2016). Regarding the amount of HEI by type of Accreditation, the Faculty was predominant with 5 (42%), University Center with 4 (33%) and University 3 (25%). As for the number of students, the University Centers had 16,800 (51%), Universities 12,345 (37%) and Colleges 3,900 (12%), totaling 33,135 students enrolled in the various attendance courses held by the IES Private Holders The research presented as a contribution the diagnosis of the adoption of good corporate governance practices of the IBGC (2016) by the IES Private Foundations of the South of Minas Gerais, since Corporate Governance is one of the guiding principles of good governance. management and transparency in the use of resources